THE EFFECT OF LONGITUDINAL VIBRATION ON LAMINAR FORCED CONVECTION HEAT TRANSFER IN A HORIZONTAL TUBE (Journal of Engineering, 2006)
The effect of longitudinal vibration on the laminar forced convection heat transfer in a horizontal tube was studied in the present work. The flow investigated is an internal, laminar, incompressible, developing, steady and oscillatory flow. The vibration vector was parallel to the fluid flow direction. The boundary layer was studied in the entrance region for Prandtl numbers greater than one and the hydrodynamic boundary layer grows faster than thermal boundary layer. The governing equations which used were momentum equation in the axial direction, continuity and energy equation. The finite difference technique was introduced to transform the partial differential equations into algebraic equations and the later equations were solved using the upwind scheme. The vibrational Reynolds number used as indication to the vibration and vibrational velocity which is used as boundary condition. The effect of vibration on laminar forced convection heat transfer is to increase the local and average Nusselt number when the vibrational Reynolds number increases; therefore, heat transfer coefficient increases too. Correlations for local Nusselt number with vibration concluded for constant wall temperature and constant heat flux